Meta-Theatricality and the Collapse of Illusion in Postmodern Plays - Hulaib, Mohanad Naeem (International Consortium of Education and Culture Research Studies, 2025)
General Background: Postmodern theatre is characterized by the intentional exposure of its own artifice, challenging conventional dramatic illusion and encouraging audiences to question the nature of representation. Specific Background: Plays such as Waiting for Godot, The Bald Soprano, and The Vagina Monologues employ meta-theatrical strategies including fourth-wall breaks, nonlinear narratives, and intertextual references to foreground self-reflexivity and destabilize narrative coherence. Knowledge Gap: Although extensive scholarship has examined meta-theatricality, limited studies systematically connect these strategies to the broader cultural and philosophical conditions that define postmodern dramaturgy. Aims: This study analyzes how meta-theatrical techniques in selected postmodern plays contribute to the collapse of theatrical illusion and reveal deeper existential, aesthetic, and cultural concerns. Results: Close analysis shows that fragmentation, irony, and self-referential performance consistently destabilize realism, reposition spectators as active interpreters, and foreground the artificiality of theatrical space. Novelty: The study demonstrates that meta-theatricality does not merely break illusion but becomes a structural method for questioning authenticity, truth, and meaning within postmodern culture. Implications: These findings highlight meta-theatre as both an artistic and cultural practice that reshapes audience perception, challenges representational norms, and reinforces theatre’s ongoing relevance as a site for critical reflection in a rapidly shifting cultural landscape.Highlight : Shows the collapse of theatrical illusion through self-reflexive techniques. Uses meta-theatrical strategies to disrupt dramatic realism. Highlights the audience’s awareness of unstable representation. Keywords : Meta-Theatricality, Collapse, Illusion, Postmodern, Plays